Expert System For Diagnose Covid19 Using Certainty Factor Method - Lukman Nulhakim; Doni Andriansyah (Universitas Medan Area, 2021)
AbstractAt the end of 2019 the world was shocked by the emergence of a new type of virus from the Corona family, namely the Novel Coronavirus (2019-nCoV) which had never been previously identified in humans, later known as Coronavirus disease 2019 (Covid-19). Early symptoms in people with Covid-19 include fever, cough and shortness of breath, similar to flu and cough symptoms in general, making it difficult to detect early. The certainty factor method can measure a certainty and uncertain thing. Research with certainty factor methods has been carried out to diagnose a disease based on the symptoms experienced. Types of diseases are focused only on types of diseases with almost the same symptoms, namely Upper Respiratory Tract Infection, Pneumonia, and Covid-19. The purpose of this study is to build an expert system application that can be accessed online to detect early symptoms experienced by sufferers. Based on the results and discussion, the expert system application can run well and the results of manual CF calculations are the same as the results of CF calculations on the system.